2019
DOI: 10.1002/ecs2.2891
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the seasonal energy balance in Asian black bears and associated factors

Abstract: Energy balance (i.e., energy intake minus energy expenditure) is an essential factor when evaluating an animal's nutritional state. We aimed to identify periods of the year that are most important for Asian black bears (Ursus thibetanus) in terms of energy balance. We estimated bears’ daily energy balance by estimating energy intake based on the energy content (kcal/g) of major food items, their average ingestion rate (g/min), and daily feeding time (min) and by estimating energy expenditure using an equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The energy balance is an essential factor to evaluate the nutritional state of bears (Robbins et al., 2004). The energy balance of Asian black bears has previously been suggested to follow a seasonal, bimodal pattern, dropping from spring to summer and increasing from summer to a peak in autumn (Furusaka et al., 2019). In particular, decreased food consumption by Asian black bears in summer (i.e., June and July) was associated with a large decrease in their energy balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy balance is an essential factor to evaluate the nutritional state of bears (Robbins et al., 2004). The energy balance of Asian black bears has previously been suggested to follow a seasonal, bimodal pattern, dropping from spring to summer and increasing from summer to a peak in autumn (Furusaka et al., 2019). In particular, decreased food consumption by Asian black bears in summer (i.e., June and July) was associated with a large decrease in their energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, decreased food consumption by Asian black bears in summer (i.e., June and July) was associated with a large decrease in their energy balance. One factor that has been proposed to explain this is low availability of food resources during this time of the year (Fuchs et al., 2019; Furusaka et al., 2019). However, our results suggest that within this period, bears decreased foraging activities on social days compared with solitary days, which accounted for about half of the days in the mating season in one male and both females.…”
Section: Discussionmentioning
confidence: 99%
“…Interannual differences in the consumption of hard mast are due to the annual fluctuation of mast production (Koike et al 2012, Naganuma et al 2020). In general, Asian black bears seem to follow an energy‐conserving strategy during the hyperphagia by eating large amounts of hard mast with high carbohydrate content (i.e., a food source that is relatively predictable in time and space) rather than searching for deer carcasses, which requires extensive travel time (Furusaka et al 2019). Although our models are unable to directly compare deer consumption between seasons, bears may reduce deer consumption from the deer birthing season to the rutting season because of this strategy (Table 1; Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…We required estimates of the dietary proportion of mass that bears consumed to calculate macronutrient compositions. Therefore, studies where foods were originally reported as the proportion of dry mass of diet or were estimable after applying fecal correction factors (CFs) to percent fecal volume or dry weight estimates were included (Baldwin & Bender, 2009 ; Bojarska & Selva, 2012 ; Furusaka et al., 2019 ; Hewitt & Robbins, 1996 ). We excluded studies where diet composition was assessed in ways other than percent fecal volume and dry mass.…”
Section: Methodsmentioning
confidence: 99%